Comprometimento organizacional em uma IES pública: analise do suporte organizacional como antecedente e da cidadania organizacional como consequente - Vasconcelos, Márcia Baima Taleires (2017)
Organizational commitment enables the achievement of organizational goals so that the organization can achieve efficient and effective performance. The study of this construct is indispensable for the public Higher Education Institution (HEI) that aims to adopt policies and practices of people management capable and leading its members to an adequate and high performance, as well as, a high productivity with views to the provision of the necessary services to the citizens, having as scope the social development. The present study deals with the possible relationships established between the organizational commitment, its antecedents and consequents. The general objective of this work is to investigate the influence of organizational support in the production of organizational commitment in the affective, normative and continuance dimensions and the generation of organizational citizenship in the dimensions of organizational image dissemination, creative suggestions and collaboration with colleagues as a consequent relationship. In order to achieve this general objective, the following specific objectives were elaborated: 1) to investigate the occurrence of relationships between the organizational commitment and the antecedent organizational support; 2) to verify possible differences/distinctions in investigated relations of the organizational commitment with its antecedent organizational support; 3) examine organizational citizenship as a consequence of the relationship between organizational commitment and antecedent organizational support, and 4) analyze possible differences in the relationships established between the dimensions of organizational commitment and the dimensions of organizational citizenship. In order base the present study, we chose the conceptual framework of Meyer and Allen (1991, 1993). The developed research is characterized by being quantitative in terms of the purposes and exploratory, descriptive and explanatory in what concerns its means, it is also a cross-section survey. The population universe comprises the members of the intermediate management body of a public HEI, in all campi of the Institution and the sample universe comprises 265 public servants, occupying an intermediate level management function, equivalent to 36% of the estimated population. The results pointed out that organizational support is a predictor of organizational commitment only to the affective and normative dimensions of this construct, being also a predictor of the effect generated by relations between these two variables (organizational commitment and organizational support), manifested in the form of organizational citizenship.